(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The article addresses a critical phase in the trajectory of the Algerian national movement, spanning from 1939 to 1945. While the world was engulfed in a conflict between the Allies and the Axis, Algerians, like other colonized peoples, found themselves drawn into this struggle, even though it was not directly relevant to them. On the eve of this war, France mobilized all its economic and social resources for the French war effort, transferring agricultural and industrial wealth to the war fronts and enlisting thousands of Algerians as soldiers and factory workers in war industries. Politically, under martial law, French policy aimed to suppress the significant developments in the national movement that had been emerging since the late 19th and early 20th centuries. After World War I, Emir Khaled Al-Jazairi began advocating openly for Algerian rights, marking the first instance of political activism on behalf of Algerians. This political momentum continued intensively, beginning in France itself, where Messali Hadj and other Algerian immigrants founded the North African Star in 1926 and the Algerian People’s Party in 1937. Additionally, a group of scholars established the Association of Algerian Muslim Scholars in 1931, while, in 1927, a group of elite deputies formed the Federation of Algerian Muslim Elected Representatives. During World War II, France froze all political and press activities, dissolving parties such as the Algerian People’s Party and the Association of Algerian Muslim Scholars, and targeted nationalists from all sides. Messali Hadj was imprisoned again, Bashir Ibrahimi was exiled to the desert, and Abdelhamid Ben Badis was placed under house arrest. However, these repressive measures did not affect Ferhat Abbas, who was granted considerable freedom. Abbas utilized this freedom to represent the Algerian national movement, seeing the Allies’ landing in Algeria on November 8, 1942, as a turning point. He viewed it as an opportunity to bring the Algerian cause before the Allies. Thus, in the "Algerian Manifesto" issued on February 10, 1943, he called for the Allies to apply the principle of "the right of peoples to self-determination" outlined in the Atlantic Charter on August 14, 1941. Later, on March 14, 1944, he solidified this by organizing the Algerian national movement under the "Friends of the Manifesto and Liberty." This dynamic sequence of rapidly unfolding events culminated tragically in the demonstrations of May 8, 1945, which concluded a critical phase in the Algerian national movement and ushered in a new era marked by numerous developments and transformations.